Psychological Disposition and Cultural Constraints to Female Participation in Higher Education: A Study of Selected University Women - Fagbemi, Funmi Mowaiye- (NIU Journal of Social Sciences, 2017)
In Europe, America and Latin America, statistics show that the ratio of girls and boys at the primary and secondary levels of education are proportionate. In Nigeria, this is not the case, but rather, female participation in education is usually more pathetic in the so-called unfeminine fields. Yet, females constitute approximately fifty percent of the country’s population. The present study is an exploration of cultural factors and the disposition of women in Nigerian Universities, to some selected factor. The findings revealed that there are many constraints in the academic path of many females and that most of them were trained for the home roles.